MODEL DAN DAMPAK MOBILISASI POLITIK PEMILIHAN KEPALA DESA (Studi Kasus: Desa Bontomatinggi Kabupaten Maros Sulawesi Selatan Tahun 2016) - La Ode Muhammad Elwan (Universitas Halu Oleo, 2018)
The purpose of this study was to determine the impact of village head elections after the implementation of the Bontomatinggi Village Head election in Maros Regency in 2016. The research method used is a qualitative research method with a descriptive approach to analysis and using the theory of political mobilization, data collection using interview, observation and documentation techniques. The data analysis technique used by the author is a qualitative data analysis technique that is by searching and compiling systematically from the results of interviews, observations and documentation and then selecting the data needed and making conclusions that are easy to understand.Based on the results of the study, direct and indirect mobilization models and the impacts that occurred in the community after the election of Maros Regency Bontomatinggi Village Chief occurred several models such as socialization of village head candidates, mass mobilization, open campaign (direct mobilization model) and dialogical campaigns conducted from home to home (direct mobilization model). The impact of the model and after the election is that there is an unnatural mobilization model such as intimidation and threats to voters, giving facilities and money politics, black campaigns and spreading slander. Some of the factors that influence the voters' decision to elect a village head are the lack of education level of the community, mobilized communities are afraid that there will be violence and utterances of hatred from the candidates and the successful team if they do not follow their wishes. Keywords : Political Mobilization Model, the impact of village head elections